Решение обратной задачи электрометрии скважин повышенного вертикального разрешения - Миронцов, Н.Л. (Доповіді НАН України, 2020)
Предложен новый быстрый способ решения обратной задачи многозондовой электрометрии скважин, который позволяет учитывать количественный вклад измерения каждого зонда в окончательный результат. Разработан и реализован в программном виде соответствующий алгоритм решения обратной задачи. Показано, что предложенный подход позволяет также существенно улучшать вертикальное разрешение метода в целом. Приведен пример сравнения различных результатов решения обратной задачи бокового каротажного зондирования и бокового каротажа при изменении вклада измерения каждого зонда в окончательный результат. Запропоновано новий швидкий спосіб розв'язання оберненої задачі багатозондової електрометрії свердловин, який дозволяє враховувати кількісний вклад вимірювання кожного зонда в остаточний результат. Розроблено та реалізовано в програмному вигляді відповідний алгоритм розв'язання оберненої задачі. Показано, що запропонований підхід дозволяє істотно покращувати вертикальну роздільну здатність методу в цілому. Наведено приклад порівняння різних результатів розв'язання оберненої задачі бокового каротажного зондування і бокового каротажу при зміні вкладу вимірювання кожного зонда в остаточний результат. A new fast method of solving the inverse problem of multiprobe electrometry of wells is proposed. It allows one to account for the quantitative contribution of measuring each probe to the final result. The algorithm for solving the inverse problem has been developed and implemented in a software. It is shown that the proposed approach can also significantly improve the vertical resolution of the method as a whole. An example of the comparison of various results of solving the inverse problem of lateral logging sounding and lateral logging, when changing the contribution of the measurement of each probe to the final result, is given. It is concluded that the use of a quick method for solving the minimization of the residual functional, if combined with the ability to consider the contribution of each probe of the multiprobe electrometric complex to the final result of solving the inverse problem, makes it possible to increase the accuracy of a quantitative interpretation. It is also shown how the developed algorithm and the corresponding created software make it possible to increase the accuracy of determining the geoelectric parameters of oil and gas reservoirs. The results of the work were introduced into the production at a number of commercial geophysical organizations.